Labor shares in the EU: Sectoral effects and the role of relative prices - István Kónya; Judit Krekó; Gábor Obláth (Hungarian Academy of Sciences, Institute of Economics, 2019)
The paper studies the labor share among countries of the European Union, with a particular attention to newer member states of Central and Eastern Europe (CEEU). After discussing methodological issues in the computation of the labor share, we present various stylized facts at the country level, and also for broad sectors within the aggregate economy. We find that CEEU countries typically have lower labor shares, both in the aggregate and at the sectoral level. Structural change, while quite pronounced among the CEEU economies, plays only a minor role in the evolution of the labor share. The exception is agriculture, which for some countries have a sizable impact on the level and dynamics of the labor share - partly because of important measurement problems. We also document links between productivity, the relative prices of consumption and investment, and the labor share. In particular, we find that a significant part of the difference in conventionally measured labor shares between the more developed EU countries and less developed CEEU countries can be attributed to differences in relative prices. We discuss possible explanations, and show that given reasonable assumptions, a simple two-sector model is able to account for the main findings.
Keywords: E24; J30; O11; 330; labor share; development; labor productivity; relative prices; European Union